(untitled) (UNED Research Journal, 2018)
There are no reports addressing the characterization of grains of maize landraces from Costa Rica. From April to August 2013, we collected grain samples of maize (Zea mays L.) landraces (also called creole maize) in Nicoya and Hojancha cantons, Guanacaste province, Costa Rica, through visits to different local growers. We characterized grains of five maize landraces (Amarillo, Congo, Piquinitillo, Pujagua and Rocarina), considering both qualitative (three) and quantitative (seven) variables. There were statistically significant differences between phenotypes for quantitative variables. Data show a wide variability with respect to grain length (9,10 – 11,96 mm), grain width (6,41 – 9,12 mm), grain thickness (3,27 – 4,49 mm), grain length/width ratio (1,17 – 1,77), grain length/thickness ratio (2,24 – 3,69), grain width/thickness ratio (1,71 – 2,39), and weight of 100 grains (16,80 – 30,60 g). This is the first report about the existence of Piquinitillo and Rocarina landraces in Costa Rica, as well as the first report about grain characterization of maize landraces from Costa Rica.